Assessment of Ecological Conditions and Potential of Pastures, Meadows and Steppes Landscapes of Georgia - Elizbarashvili , Nodar; Grigolia, Lado; Sandodze, Gela (Global Journal Of Botanical Science, 2022)
The natural diversity of Georgia is outstanding in the world. This is particularly true with the subtropical and moderate belts of the country presenting over seventy natural landscapes, from humid subtropical or light semiarid forests through moist and Alpine landscapes. Such a variety is the result of several factors, with the following ones being most important: geographical location (location along the border of the tropical and moderate belts), effect of the Black Sea (which never freezes), altitudinal zoning (up to 5200 ml) and several-thousand-year-long history of the economic use of the territory. The highly diverse landscapes of Georgia complicate the study of the geographical-ecological (geo-ecological) properties of the country. Among such properties, horizontal and vertical structure of landscapes, energy and substance transformation in the landscape (functioning), forms and scales of influence on the landscapes, landscape stability and function, and landscape condition and potential have a particular importance. The condition of landscapes is determined by the forms and scales of external influence. The character of influence can be considered by the ability of self-regeneration of the landscape structure. It is admitted that if the impact applies to the biologic components only, the landscape preserves the self-generation ability. The self-regeneration mechanism is impossible to maintain if: 1. the influence coincides with or stimulates (increases) the negative natural processes; 2. The basic landscape creator component or relief and climate is under the impact; 3. One ecosystem is changed by another equivalent one. Potential of landscapes is a spatial-and-time category ensuing from the natural properties of the landscapes, results of anthropogenic impact and kinds and trends of the territory use. In some cases, they attribute the landscape potential to the terms of landscape comfort and quantitative indicators of the landscape structure and components, what gives a too general view of the landscape potential. Condition and potential of landscapes are important issues of territorial planning, eventually determining the forms of use, protection and sustainable development of pastures, meadows and steep landscapes. The article evaluates the ecological condition and potential of those landscapes (ecosystems - pastures, meadows and steppes) of Georgia, which are greatly influenced by both human economic activity and climate change trends.